Electrically assisted forming modeling and control - Salandro, Wesley A.; Jones, Joshua J.; Bunget, Cristina; Mears, Laine; Roth, John T. (Springer International Publishing, 2015)
Maximizing reader insights into the latest research findings and applications of Electrically-Assisted Forming (EAF) - whereby metals are formed under an electric current field - this book explains how such a process produces immediate improved formability of metals beyond the extent of thermal softening, and allows metals to be formed to greater elongation with lower mechanical energy as well as allowing for lightweight brittle metals such as magnesium and titanium to be formed without external heating or annealing, enabling the more effective use of these lightweight metals in design. Including case studies that illustrate and support the theoretical content and real-world applications of the techniques discussed, this book also serves to enrich readers understanding of the underlying theories that influence electro-plastic behaviour. The authors have extensive experience in studying Electrically-Assisted Forming and have written extensively on the topic with publications including experimental works, technical briefs, conference proceedings, journal articles, and analytical models.